1999
DOI: 10.1097/00004647-199908000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mediators and Stroke: New Opportunities for Novel Therapeutics

Abstract: Contrary to previous dogmas, it is now well established that brain cells can produce cytokines and chemokines, and can express adhesion molecules that enable an in situ inflammatory reaction. The accumulation of neutrophils early after brain injury is believed to contribute to the degree of brain tissue loss. Support for this hypothesis has been drawn from many studies where neutrophil-depletion blockade of endothelial-leukocyte interactions has been achieved by various techniques. The inflammation reaction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
610
1
9

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 864 publications
(640 citation statements)
references
References 185 publications
11
610
1
9
Order By: Relevance
“…Several studies have reported prominent changes in proinflammatory cytokines following stroke. [20][21][22] The proinflammatory cytokines interleukin (IL)-1, tumor necrosis factor a (TNF-a), IL-6 and IL-8 have all been shown to be involved in the initiation or amplification of the inflammatory response in patients following acute cerebral ischemia. Interestingly for our purposes, some studies on experimental models have suggested that inflammatory mediators, such as the cytokine IL-1, might contribute to the extent of cerebral ischemia through their effects on specific limbic pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported prominent changes in proinflammatory cytokines following stroke. [20][21][22] The proinflammatory cytokines interleukin (IL)-1, tumor necrosis factor a (TNF-a), IL-6 and IL-8 have all been shown to be involved in the initiation or amplification of the inflammatory response in patients following acute cerebral ischemia. Interestingly for our purposes, some studies on experimental models have suggested that inflammatory mediators, such as the cytokine IL-1, might contribute to the extent of cerebral ischemia through their effects on specific limbic pathways.…”
Section: Resultsmentioning
confidence: 99%
“…As an analogy to hippocampal neurons [10], we speculate that an ischemia-induced alteration of GluR2 expression in Deiter's neurons induced cell death. Although further investigations are required to clarify the mechanisms underlying this selective vulnerability and delayed neuronal damage, they may also be related to several other factors such as the degree of cerebral hypoperfusion after reperfusion [11], inhibition of protein synthesis [12], neutrophil infiltration following reperfusion [13], free radical production [14], dysfunction of the mitochondrial shuttle system [15] or apoptosis [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Because there are multiple mechanisms involved in neuronal injury after ischemia, it is appropriate to consider using pharmacological agents that affect multiple mechanisms simultaneously or sequentially (for reviews, [4,9,22,24]). Therapeutic strategies have been designed typically to affect only one of several mechanisms in the ischemic cascade, but combinatorial therapies are likely to be more effective than monotherapy, as in the treatment of HIV/AIDS [10,14].…”
Section: Discussionmentioning
confidence: 99%